PARAGRAPH UTILIZING ON BBC NEWS IN ANALYSING SIMPLE PRESENT TENSE: A MORPHOLOGICAL APPROACH - Mutakhirani Mustafa (JOURNAL OF LANGUAGE, 2023)
The purpose of this study is to investigate the paragraphs utilization on BBC News in analyzing simple present tense by using morphological approach. The object of the research was non-EFL students of  IAIN Syekh Nurjati Cirebon. The sample of the research was 32 students. This research implemented a descriptive method, an action research. An action research is a method of testing theories using the real world. To make the students understand the simple present tense therefore the researcher applied a morphological approach to analyze simple present tense.  The steps of the research are first the students are asked to read the paragraph of the BBC News and then find the simple present in which the verbs experienced affixation -s, -es, and -ies . The next step is that the students complete the missing word. Data collection is taken from the students' answers. The students do the activity regularly to know the influence of the treatment.  The resulting score of the post-test showed that the ability of the students in analyzing simple present tense in English News by using BBC News application and using morphological approach was effective. It indicated that all treatments successfully helped the students in analyzing simple present tense.   Based on the score after the implementation of the treatment, the analyzing skill of the students improved. Adding -s, -es, and -ies on the verbs in the simple present in the paragraph of the news on BBC News is a morphological process.